2021
DOI: 10.1126/sciadv.abc9917
|View full text |Cite
|
Sign up to set email alerts
|

A polymeric approach toward resistance-resistant antimicrobial agent with dual-selective mechanisms of action

Abstract: Antibiotic resistance is now a major threat to human health, and one approach to combating this threat is to develop resistance-resistant antibiotics. Synthetic antimicrobial polymers are generally resistance resistant, having good activity with low resistance rates but usually with low therapeutic indices. Here, we report our solution to this problem by introducing dual-selective mechanisms of action to a short amidine-rich polymer, which can simultaneously disrupt bacterial membranes and bind to bacterial DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 67 publications
1
69
0
Order By: Relevance
“…Such "binding moieties along a line" peptidomimetic design has already been successfully employed in pathogenic DNA/RNA binding, 33 and we indeed observed enhancement on DNA binding strength of PAPIs using PI fluorescent titration experiments (Figure 2a and Figure S13). The affinity of PAPI 1-2 toward M. smegmatis genomic DNA (K i = 2.8 μM against PI-DNA, per bisamidine moiety) were comparable to the oligoamidine we reported recently, 12 and were much higher than monomeric DAPI (K i = 94 μM), indicating the successful enhancement in DNA binding strength through a multivalent approach. Yet, similar to DAPI dye, PAPIs could also gain fluorescence upon binding to dsDNA (345 nm/455-510 nm, Figure S14), which would facilitate the observation of its intracellular binding behavior.…”
Section: Conformation Simulation Of the Hit Peptidomimeticsupporting
confidence: 79%
See 3 more Smart Citations
“…Such "binding moieties along a line" peptidomimetic design has already been successfully employed in pathogenic DNA/RNA binding, 33 and we indeed observed enhancement on DNA binding strength of PAPIs using PI fluorescent titration experiments (Figure 2a and Figure S13). The affinity of PAPI 1-2 toward M. smegmatis genomic DNA (K i = 2.8 μM against PI-DNA, per bisamidine moiety) were comparable to the oligoamidine we reported recently, 12 and were much higher than monomeric DAPI (K i = 94 μM), indicating the successful enhancement in DNA binding strength through a multivalent approach. Yet, similar to DAPI dye, PAPIs could also gain fluorescence upon binding to dsDNA (345 nm/455-510 nm, Figure S14), which would facilitate the observation of its intracellular binding behavior.…”
Section: Conformation Simulation Of the Hit Peptidomimeticsupporting
confidence: 79%
“…To enhancement peptidomimetics' effectiveness against mycobacteria, structural adjustments should be made to counter these bacteria's unique defensive fortifications: (1) mycobacteria have slow reproduction rate 15 and low sensitivity toward many antibiotics in "dormant state", 7 and (2) mycobacteria have thick and highly hydrophobic enclosures to protect themselves. As shown in Figure 1a, for the former we have already demonstrated that the "membrane-plus-DNA" dual-targeting strategy was effective for those "dormant persisters", 12 ; for the latter, a straightforward solution may be the preparation of more hydrophobic antimicrobial agents so that they can show higher affinity toward mycobacteria. Thus, our aim was narrowed down to the design of dual-mechanistic peptidomimetics with an emphasis on increased overall hydrophobicity.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to high therapeutic indices, the SNAPPs displayed low toxicity towards mammalian cells [115]. A recent study by Silei Bai et al [116] has also shown a short, amidine-rich antimicrobial polymer with dual-selective mechanisms of action against harmful "Superbugs", including disrupting bacterial membranes and binding to bacterial DNA. This so-called oligoamidine showed high therapeutic indices against many bacterial types, including the ESKAPE pathogens and clinical isolates resistant to multiple drugs, with no observable resistance generation.…”
Section: New Polymer Mimics Of Hdps-highlightsmentioning
confidence: 99%